Rancangan sistem e-maintenance elektronika bandara berbasis web dan qr code studi kasus bandara douw aturure nabire - Asrul Saefullah Kadir; M. Arif Sulaiman; Toni (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
Maintenance of airport electronic equipment is a critical aspect in ensuring flight safety, security, and operational continuity. However, the recording and reporting of electronic equipment maintenance activities at the Douw Aturure Nabire Class II Airport Management Unit (UPBU) are still conducted manually using physical logbooks. This condition leads to several issues, including the risk of data loss, difficulties in tracing maintenance history, and limited technical supervision.This study aims to design and implement a web-based E-Maintenance system for airport electronic equipment integrated with Quick Response (QR) Code technology to improve the efficiency and reliability of maintenance record management. The system development method applied in this study is Agile Software Development using the Feature Driven Development (FDD) approach.The developed system supports maintenance data entry by technicians, equipment identification through QR Code scanning, technical validation of maintenance reports by supervisors, and digital generation of maintenance reports. The results of system testing using the Black Box Testing method indicate that all system functionalities operate according to user requirements and system design specifications.Based on these results, it can be concluded that the developed E-Maintenance system is capable of improving the efficiency of maintenance data recording and management, facilitating maintenance history tracking, and enhancing data reliability through a structured technical validation mechanism